The Prevalence of Gastrointestinal Parasites in Native Dogs in Palestine - Rateb A. Othman; Sameh Abuseir (Iranian Journal of Parasitology, 2021)
Background: Dogs play an important role in transmission of parasites and zoonotic diseases, especially in developing countries. We aimed to investigate the prevalence of internal parasites in stray and pet dogs in Palestine.